PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN LAMPU OTOMATIS TERHADAP HASIL DAN MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH FISIKA LISTRIK - Romadon R.; Eka Maryam (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
Research aims to determine the influence of the use of automatic light learning media in the learning activities, especially on the subject of electrical physics. The subject of this study was a student of Computer Engineering study Program STMIK Dian Cipta Cendikia Kotabumi. This research uses quantitative research methods i.e. data related to the numbers obtained using statistical calculations. Data collection is done by test and poll. Data analysis techniques use a discrete analysis whereas for hypothesized testing in this study using Test T. Based on the results of analysis can be concluded that there is increased motivation to learn to use the learning media in courses Electrical physics in the students of Prodi Computer Engineering, STMIK Dian Cipta Cendikia Kotabumi Semester even year 2019. From the poll's assessment obtained r_hitung or r_xy = 0.63 while r_tabel = at N = 25 and α = 0.05 of critical table of product moment, r_tabel = 0.45 to r_hitung > r_tabel (0.63 > 0.45). From the analysis, it can be sorted by the correlation value between the X and Y values in the word Gori with the correlation coefficient between intervals 0.6 – 0.8. In the result, there is an increase in the score of 19.9 or 49.2% of the initial average score.